Advanced maternal age and occurrence of infant death: Brazilian ecological study - Larissa Muzel de Sousa; Ivana Regina Gonçalves; Ana Paula Pinho Carvalheira; Ana Beatriz Henrique Parenti; Hélio Rubens de Carvalho Nunes; Cristina Maria Garcia de Lima Parada (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To analyze the evolution of the characteristics of infant deaths registered in Brazil among women with advanced maternal age. Method: Ecological time series study using secondary data from the Mortality Information System on the evolution of infant deaths from 2011-2020. The variables assessed included: maternal, infant gestational and birth characteristics, as well as data related to death. The behavior of the variables was assessed using simple linear regression models with a normal response, with the year as the independent variable in each of the subpopulations. Results: The studied sample consisted of 30,843 infant deaths among women aged 35 years or over. There was a decreasing trend for the variables race/white skin color, living in the southern region of the country, lack of schooling of the mother or up to 7 years education, paid work and vaginal delivery; there was an increase trend for the variables: race/brown skin color, mother’s education level equal to or greater than 8 years and low birth weight. Conclusion: The analysis revealed distinct patterns regarding sociodemographic and maternal and child health factors, highlighting the complexity of infant mortality trends and the importance of effective collective approaches.